Production cost of soybean crop under phytopathogens management and boron doses - Silva, Marco Antônio da; Silva, Reiner Pimenta da; Souza, Epitácio José de; Bertotti, Jalel Augusto Algeri; Nuñez, Daniel Noe Coaguila (Brazilian Journal of Science, 2022)
Soybean (Glycine max (L.) Merr.) is one of the most economically important crops in the world, and Brazil is the world’s largest producer of the grain. The influence of the crop is mainly defined by the interaction of the plant with the environment and management, mainly phytosanitary and nutritional management. Thus, the objective was to evaluate the production costs and their effects on the productivity of the consortium methods of chemical or biological products for the management of phytopathogens, as a function of B doses applied in the desiccation and/or applied later supplementation in R1 (beginning of flowering). The experiment was installed under a no-tillage system, at the Rio Verdinho Três Barras farm, Rio Verde, Goiás, Brazil, from October 2021 to March 2022, with a spacing of 0.45 m using the soybean cultivar ’DM 68i69 IPRO’, recommended for the region. The experimental design used was in randomized blocks, with 11 treatments and four replications. The treatments consisted of 2 phytosanitary managements (seed treatment with biological products and standard treatment of most producers in Southwest Goiás) to control phytopathogens and 5 doses of boron (0; 0.25; 0.50; 0.75 and 1.0 L ha-1) applied during desiccation and/or applied after supplementation in R1. At the end, final productivity and production costs were evaluated. Data were analyzed by analysis of variance using the F test p < 0.05 and means were revealed using the Duncan test p < 0.05. To estimate the cost of production, the structure of total operating cost of production, proposed by the Institute of Agricultural Economics – IEA, was used. Higher boron applications in desiccation at doses 1 L ha-1 or 0.75 L ha-1 and lower boron doses in stage R1 significantly increase soybean grain productivity. The tested treatments did not influence the total operating cost (TOC), the relative total operating cost (COEr), the gross revenue (RB), the effective operating profit (LOE), the total operating profit (LOT), the profitability, as well as the production estimate and equilibrium estimate. The TOC estimate for soybean grown in Rio Verde, Goiás, Brazil was R 10,616.52 ha-1 with yields of up to 95 bags ha-1.